Myofunctional Treatment of Anterior Crossbite in a Growing Patient. (8th October 2020) - Pellegrino, Marianna; Cuzzocrea, Maria Laura; Rao, Walter; Pellegrino, Gioacchino; Paduano, Sergio
Abstract : The purpose of this case report is to add another means of treatment for the anterior crossbite malocclusion in early mixed dentition. The selected functional device is an eruption guidance appliance (EGA). The analysed patient had a functional anterior crossbite, a mandibular protrusion tendency, and a normodivergent growth pattern. The early treatment was suggested to correct the malocclusion and avoid unfavourable occlusal conditions that could end in a class III malocclusion growth pattern. After 18 months of treatment, with night-time use, the malocclusion was completely resolved. This therapy strategy allowed the correction of the sagittal jaws' relationship and maximum control of the vertical dimension. After 2 years of follow-up, the results were preserved. The peculiarity of this kind of intraoral orthodontic tools is the use of the erupting forces rather than the active forces. This early treatment of anterior crossbites with EGA may be considered an effective treatment approach for achieving good functional and aesthetic results.